Relacje polsko-rosyjskie w retoryce politycznej obchodów rocznic zbrodni katyńskiej po 1989 roku. Perspektywa politolingwistyczna - Czubaj-Kuźmin, Sylwia (Przegląd Politologiczny, 2018)
Polish-Russian relations seem to be heavily burdened by historical experience. History in- fluences the present not only indirectly, via historical facts, but also via the ways of commem- orating them. Referring to their memories, social groups strengthen the sense of their own uniqueness and cultural identity. One of the ways to commemorate events are anniversary celebrations accompanied by a certain political rhetoric. The author analyzes the texts, press releases, commentaries and an- niversary speeches given by politicians to commemorate the Katyñ massacre published by the „Gazeta Wyborcza” and „Rzeczpospolita” daily in April 1990, 2000 and 2010. Among the figures of memory identified in the analyzed texts which are typical of the Pol- ish-Russian dialogue concerning the Katyñ issue over the period of 1990–2010, there prevails a certain group of topoi appropriated by the language of politics from Christianity, and pre- cisely from the sacrament of confession. These topoi are based on reconciliation and compen- sation. Other topoi involve those of a victim, righteous Russian or a common field of memory.